Deciphering the Association of Cytokines, Chemokines, and Growth Factors in Chondrogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells Using an ex vivo Osteochondral Culture System - Jafri, Mohammad Alam; Kalamegam, Gauthaman; Abbas, Mohammed; Al-Kaff, Mohammed; Ahmed, Farid; Bakhashab, Sherin; Rasool, Mahmood; Naseer, Muhammad Imran; Sinnadurai, Vasan; Pushparaj, Peter Natesan (Frontiers in Cell and Developmental Biology, 2020)
Osteoarthritis (OA) is a chronic degenerative joint disorder associated with degradation and decreased production of the extracellular matrix, eventually leading to cartilage destruction. Limited chondrocyte turnover, structural damage, and prevailing inflammatory milieu prevent efficient cartilage repair and restoration of joint function. In the present study, we evaluated the role of secreted cytokines, chemokines, and growth factors present in the culture supernatant obtained from an ex-vivo osteochondral model of cartilage differentiation using cartilage pellets, (CP), bone marrow stem cells (BM-MSCs) and/or BM-MSCs + CP. Multiplex cytokine analysis showed differential secretion of growth factors (G-CSF, GM-CSF, HGF, EGF, VEGF); chemokines (MCP-1, MIP1α, MIP1β, RANTES, Eotaxin, IP-10), pro-inflammatory cytokines (IL-1β, IL-2, IL-5, IL-6, IL-8, TNFα, IL-12, IL-13, IL-15, IL-17) and anti-inflammatory cytokines (IL-4, IL-10) in the experimental groups compared to the control. In silico analyses of the role of stem cells and CP in relation to the expression of various molecules, canonical pathways and hierarchical cluster patterns were deduced using the Ingenuity Pathway Analysis (IPA) software (Qiagen, USA). The interactions of the cytokines, chemokines, and growth factors that are involved in the cartilage differentiation showed that stem cells, when used together with CP, bring about a favorable cell signaling that supports cartilage differentiation and additionally helps to attenuate inflammatory cytokines and further downstream disease-associated pro-inflammatory pathways. Hence, the autologous or allogeneic stem cells and local cartilage tissues may be used for efficient cartilage differentiation and the management of OA.